Molecular Characterization of 14-3-3 Zeta Gene in Musca domestica (Diptera: Muscidae) and Its Roles in Response to Bacterial Infection. Issue 5 (31st October 2022) - Jiao, Zhenlong; Yang, Yujin; Xiu, Jiangfan; Shang, Xiaoli; Peng, Jian; Guo, Guo
Abstract: The 14-3-3 gene plays important role in many biological processes, including cell survival, apoptosis, and signal transduction. However, function of the 14-3-3 homologous gene in Musca domestica remains unclear. Here, we identified and characterized the 14-3-3ζ of M. domestica . We found that Md14-3-3ζ gene was highly homologous with other close insects. The qRT–PCR analysis revealed that the Md14-3-3ζ was highly expressed in adults, and was expressed predominantly in hemocytes and fat body. Meanwhile, the expression of Md14-3-3ζ was up-regulated after injecting Escherichia coli and Staphylococcus aureus. Moreover, the recombinant protein rMd14-3-3ζ strongly inhibits the growth of E. coli and S. aureus . Notably, the rMd14-3-3ζ inhibits E. coli and S. aureus by permeating the cell membrane. Taken together, our findings suggested that Md14-3-3ζ is involved in the immune response against bacteria through damaging the cell membrane.